Clinical Characteristics and Outcome of Patients with Distal Anterior Cerebral Artery Aneurysms - Bohara, Sandeep; Pradhanang, Amit Bahadur; Sedain, Gopal; Sharma, Mohan Raj (Journal of Nepal Health Research Council, 2024)
Background: Distal anterior cerebral artery aneurysms account for 3% to 7% of intracranial aneurysms. They have increased risk of premature rupture during surgery and tend to have a higher morbidity. We aim to determine the clinical characteristics, management strategies and outcomes of patients with these aneurysms who underwent microsurgical clipping at a major university hospital in Nepal.Methods: This is a retrospective study of patients with distal anterior cerebral artery aneurysms who underwent microsurgical clipping between 2012-2022. Demographic data and clinical-radiological factors like Hunt and Hess grade, aneurysm location, and modified Rankin scale score at three, six, and 12 months were collected.Results: A total of 26 aneurysms were microsurgically clipped in 20 patients in ten years. Most patients presented with Hunt and Hess grade II. Of the 26 aneurysms, 16 (62%) were in A3 segment. Six patients had associated anterior communicating artery aneurysm, two patients had middle cerebral artery aneurysm and two patients had associated arteriovenous malformation. Sixteen patients (80%) had a favorable outcome (modified Rankin scale ≤2) at 12 months follow-up.Conclusions: Aneurysms in the distal anterior cerebral artery locations are a challenging subset of aneurysms to treat. The majority of the patients had aneurysms in A3 segment and 80% patients had a favourable outcome at 12 months follow up period. Keywords: Aneurysm; distal anterior cerebral artery; outcome; subarachnoid haemorrhage.